2010
DOI: 10.1111/j.1439-0507.2009.01857.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytological analysis of the epithelial cells in patients with oral candidiasis

Abstract: The aim of this study was to evaluate oral epithelial cells of the oral mucosa infected by Candida albicans using exfoliative cytology. Oral smears were collected from clinically normal-appearing mucosa by liquid-based exfoliative cytology of 60 individuals (30 patients with oral candidiasis and 30 healthy controls matched for age and gender) and analysed for morphologic and cytomorphometric technique. Morphologically, candida-infected epithelial cells exhibited nuclear enlargement, perinuclear rings, discrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…There was also an increase of the NA:CA ratio. This study revealed that the oral mucosa of patients undergoing candida infection exhibited significant changes in the size and shape of the oral epithelial cells [28].…”
Section: Oral Mucosa Smear Results In Correlation With Conditions Sucmentioning
confidence: 99%
“…There was also an increase of the NA:CA ratio. This study revealed that the oral mucosa of patients undergoing candida infection exhibited significant changes in the size and shape of the oral epithelial cells [28].…”
Section: Oral Mucosa Smear Results In Correlation With Conditions Sucmentioning
confidence: 99%
“…2). Phagocytes produce reactive oxygen species through the pathogen-host interaction-mediated pathway [1,4,7]. Oxidative stress can result in DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress can result in DNA damage, including the oxidation of nucleosides, which could cause DNA strand breaks. One method for determining DNA damage is the micronucleus (MN) assay [7]. Exfoliated epithelial cells have been used in cytology to detect abnormal cells and to evaluate the diameters of nuclei and cytoplasm for cytomorphometric analysis and MN presence [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Loss et al . [18] demonstrated that the cellular area (CA) of the candida-infected epithelial cells was diminished compared to the non-infected controls. In addition, there was an augmentation in nuclear area (NA) and N/C area ratio.…”
Section: Discussionmentioning
confidence: 99%